FD-метод для задачі на власні значення з нелінійним потенціалом - Гаврилюк, І.П.; Клименко, А.В.; Макаров, В.Л.; Россохата, Н.О. (Інститут математики НАН України, 2007)
На основании функционально-дискретногоподхода сиспользованием полиномов Адомяна предложен численный алгоритм для задачи на собственные значения спотенциалом, состоящим из линейной части, которая зависит отнезависимой переменной, инелинейной автономной части. Доказана экспоненциальная скорость сходимости алгоритма, которая улучшается с ростом порядкового номера собственного значения. Исследовано взаимное влияние кусочно-постоянной аппроксимации линейной части потенциала и нелинейности на сходимость метода. Теоретические результаты подтверждены численными расчетами. By using the functional-discrete approach and the Adomian decomposition method, we propose anumerical algorithm to find an approximate solution of eigenvalue problem with nonlinear potential. The potential consists of the linear part depending on an independent variable and of the nonlinear autonomous part. We prove that the convergence rate of the algorithm is exponential and is improved as the order number of eigenvalue increases. We investigate the interdependency of the piecewise constant approximation of linear part of the potential and the nonlinear part and their influence on the rate of convergence of the method. We justify theoretical results by numerical examples.